Progranulin Promotes the Formation and Development of Capsules Caused by Silicone in Sprague-Dawley Rats - Zhou Y; Pang H; Wang J; Wu H; Xu Z; Liu X; Xiao Z (Dove Medical Press, 2022)
Yongting Zhou, Hao Pang, Jie Wang, Hao Wu, Zidi Xu, Xueyi Liu, Zhibo Xiao Department of Plastic Surgery, the Second Affiliated Hospital of Harbin Medical University, Harbin, People's Republic of ChinaCorrespondence: Zhibo Xiao, Email zhiboxiaodoctor@126.comBackground: Silicone implants are currently the most widely used artificial materials in plastic surgery. Capsule formation following implant application is unavoidable. When the capsule is excessively thick and strongly contracted, it can lead to obvious symptoms, clinically known as capsular contracture. Biological factors have always been the focus of research on the capsule formation. As a growth factor, progranulin (PGRN) plays an important regulatory role in wound healing, tissue fibrosis, tumor proliferation and invasion, and inflammation regulation. At present, the research on the capsule mainly involves the regulation of tissue healing and fibrosis under the influence of inflammation. Because PGRN has a regulatory role in these processes, we believe that the study of both can provide a new theoretical basis and intervention sites for monitoring and inhibiting the development of the capsule.Methods: In this experiment, the effects of different surgical operations on the content of PGRN in the surgical site and plasma of rats were detected. Sprague-Dawley (SD) rat dermal fibroblasts were co-cultured by recombinant PGRN. The effects of r-PGRN on fibroblasts were detected by 5-ethynyl-2'-deoxyuridine (EdU) assay, wound healing assay and Western blot assay. Finally, the effect of PGRN on capsule formation and contracture was studied by changing the content of PGRN in the prosthesis in rats after operation.Results: Surgical trauma and silicone implant increased plasma and local PGRN levels in SD rats. PGRN can activate the TGF-β/SMAD signaling pathway in a dose-dependent manner, thereby promoting fibroblast proliferation, differentiation and migration and inhibiting apoptosis and enhancing cell function, thereby promoting capsule formation and contracture.Conclusion: PGRN promotes the formation and contracture of the silicone implant capsule in SD rats by activating the TGF-β/SMAD signaling pathway. This discovery may provide new therapeutic targets and detection indicators.Keywords: fibrosis, fibroblast, silicone implants, implantation, TGF-&#x03B2